2014
DOI: 10.1097/nan.0000000000000074
|View full text |Cite
|
Sign up to set email alerts
|

Survey of Heat Use During Peripheral IV Insertion by Health Care Workers

Abstract: Health care workers at an academic medical center in the Midwest were surveyed to identify common practices regarding heat use during peripheral intravenous (PIV) catheter insertion. Of the 907 who responded, the majority used heat to facilitate PIV insertion at least sometimes, when veins were not easily seen or not palpable, applying a commercial dry hot pack for 2 to 5 minutes before selecting an insertion site. Heat use correlated with practice role and population, frequency of PIV insertion, and perceived… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 24 publications
1
5
0
1
Order By: Relevance
“…In terms of safety and venous dilation effects, the surface temperature of heated items applied to the skin is recommended to be 40 ± 2 °C [ 5 ]. Hot packs have the highest utilization rate for heat applications in hospitals (65%), but hot towels are also used often not only in America but also in Japan [ 8 ]. Hot towel applications include two methods: direct application of a towel moistened with hot water (moist heat) and wrapping it in a dry barrier and applying it (dry heat) [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…In terms of safety and venous dilation effects, the surface temperature of heated items applied to the skin is recommended to be 40 ± 2 °C [ 5 ]. Hot packs have the highest utilization rate for heat applications in hospitals (65%), but hot towels are also used often not only in America but also in Japan [ 8 ]. Hot towel applications include two methods: direct application of a towel moistened with hot water (moist heat) and wrapping it in a dry barrier and applying it (dry heat) [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Longduration local warming could be impractical in the busy ambulatory surgery ward; shorter-duration local warming could minimize health cost and clinicians' workload. Kiger et al 13 reported that 80% of health care workers apply local warming for no more than 5 minutes in the clinical setting. We used the heat pack for 5 minutes according to a previous study conducted by Yamagami et al, 5 which shows that 5 minutes of local warming is effective for venodilation to perform peripheral intravenous cannulation.…”
Section: Discussionmentioning
confidence: 99%
“…Heating methods such as warm towels and heat packs are used by clinicians to facilitate cannulation and venepuncture. 12,13 The Infusion Nurses Society 14 recommend that use of dry heat to improve success of venepuncture. Kiger 13 in a survey of clinicians who inserted PIVCs, found that 38% of health care workers used heat for patients who described themselves as having previous history of difficult venous access.…”
Section: Heatmentioning
confidence: 99%
“…12,13 The Infusion Nurses Society 14 recommend that use of dry heat to improve success of venepuncture. Kiger 13 in a survey of clinicians who inserted PIVCs, found that 38% of health care workers used heat for patients who described themselves as having previous history of difficult venous access. Previous research has demonstrated that localised heat improves rates of successful PIVC insertion 15 and improves the visibility and palpability of veins.…”
Section: Heatmentioning
confidence: 99%